Long-term effects of population growth on aggregate investment dynamics: selected country evidence for Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Purpose Our generation is witnessing the greatest demographic transition and Africa is at the heart of it. There is mounting concern over corresponding rising unemployment and depleting per capita income. I examine the issues in this paper from a long-run perspective by assessing the relationships between population growth and a plethora of investment dynamics: public, private, foreign and domestic investments. Design/methodology/approach Vector autoregressive models in the perspectives of vector error correction and short-run Granger causality are used. Findings In the long-run population growth will: (1) decrease foreign and public investments in Ivory Coast; (2) increase public and private investments in Swaziland; (3) deplete public investment but augment domestic investment in Zambia; (4) diminish private investment and improve domestic investment in the Congo Republic and Sudan respectively. Practical implications Mainstream positive linkage of population growth to investment growth in the long-term should be treated with extreme caution. Policy orientation should not be blanket, but contingent on country-specific trends and tailored differently across countries. The findings stress the need for the creation of a conducive investment climate (and ease of doing business) for private and foreign investments. Family planning and birth control policies could also be considered in countries with little future investment avenues. Originality/value The objective of this study is to provide policy makers with some insights on how future investment opportunities could help manage rising population growth and corresponding unemployment.
Keywords: C30; J00; O10; O40; 330; Productivity; Investment; Human capital; Causality; Africa